Energy-coupled transport across the outer membrane of Escherichia coli: ExbB binds ExbD and TonB in vitro, and leucine 132 in the periplasmic region and aspartate 25 in the transmembrane region are important for ExbD activity. - Braun, V (1996)
Ferric siderophores, vitamin B12, and group B colicins are taken up through the outer membranes of Escherichia coli cells by an energy-coupled process. Energy from the cytoplasmic membrane is transferred to the outer membrane with the aid of the Ton system, consisting of the proteins TonB, ExbB, and ExbD. In this paper we describe two point mutations which inactivate ExbD. One mutation close to the N-terminal end of ExbD is located in the cytoplasmic membrane, and the other mutation close to the C-terminal end is located in the periplasm. E. coli CHO3, carrying a chromosomal exbD mutation in which leucine at position 132 was replaced by glutamine, was devoid of all Ton-related activities. A plasmid-encoded ExbD derivative, in which aspartate at position 25, the only changed amino acid in the predicted membrane-spanning region of ExbD, was replaced by asparagine, failed to restore the Ton activities of strain CHO3 and negatively complemented ExbD+ strains, indicating an interaction of this mutated ExbD with wild-type ExbD or with another component. This component was shown to be ExbB. ExbB that was labeled with 6 histidine residues at its C-terminal end and that bound to a nickel-nitrilotriacetic acid agarose column retained ExbD and TonB specifically; both were eluted with the ExbB labeled with 6 histidine residues, demonstrating interaction of ExbB with ExbD and TonB. These data further support the concept that TonB, ExbB, and ExbD form a complex in which the energized conformation of TonB opens the channels in the outer membrane receptor proteins.